Atomic insights into the thermal decomposition mechanism and cluster growth law of nanoscale HMX and LLM-126 mixture: A ReaxFF-lg molecular dynamics study - Jianbo Fu; Mi Zhang; Kezheng Gao; Hui Ren (FirePhysChem, 2023)
In this paper, the thermal decomposition process and cluster growth law of the HMX/LLM-126 nanoscale mixture system were studied by ReaxFF-lg combined with DFT, and the thermostability of the mixture system with a molar ratio of 1:1 was investigated. The results show that clusters can be formed between HMX and LLM-126 in the mixture system, which effectively delays the cracking speed of the HMX structure. Meanwhile, NO2 generated from the initial decomposition of HMX will accelerate the denitration process of LLM-126. The decomposition process of HMX is mainly a continuous denitration until the structural ring-opening disintegration, the initial decomposition step is C4H8O8N8 => C4H8O6N7 + NO2. In contrast, the initial decomposition of LLM-126 is dominated by intramolecular hydrogen transfer reactions and the generation of dimer clusters, followed by the detachment of nitro and bitter amino groups, and finally the cleavage of the pyridine ring. The intramolecular hydrogen transfer process of LLM-126 is the transfer of H on -NH- to the adjacent nitro group. After LLM-126 was added to the HMX system, the oxygen balance of the system increased, and the N content, exothermic rate, and the number of final products decreased significantly compared with the HMX pure component system. Also, the number of clusters generated, and the maximum cluster weight increased significantly. These phenomena are important reasons for the improved thermostability of the mixture system compared to the pure HMX system. This work can provide a theoretical basis for the design and application of nanoscale high-energy thermostable mixed explosives.